Quantitative determination of human serum testosterone via isotope dilution ultra-performance liquid chromatography tandem mass spectrometry - Sun, Guang (Mol Med Rep, 2020)
Quantification of testosterone serves an important role in the differential diagnosis of androgen-related endocrine diseases. Mass spectrometry exhibits higher accuracy and lower variability than immunoassays, especially at low testosterone concentrations. The present study developed and validated an isotope dilution ultra-performance liquid chromatography tandem mass spectrometry method for determination of human serum testosterone. The serum was equilibrated with an isotopic internal standard and treated with acidic buffer to release hormones from their binding proteins. Testosterone was extracted via two serial liquid-liquid extractions. In the first stage, the lipid fractions from an acidic buffer solution were isolated using ethyl acetate and n-hexane. The organic phase was evaporated and reconstituted in a basic buffer solution. In the second stage, the polar impurities of n-hexane extraction were removed. Total testosterone in serum was quantified via ultra-performance liquid chromatography tandem mass spectrometry in multiple reaction monitoring mode with positive electrospray ionization. The coefficient of variation of the method for intra- and inter-assay was 2.13% (1.40–2.77%) and 3.44% (3.06–3.66%), respectively. The recovery ranged from 94.32 to 108.60% for different samples. The limit of detection was 0.50 ng/dl and the linear range was from 1.00 to 1,000.00 ng/dl. In addition, the extraction efficiency in three different levels of quality control of the serum ranged from 85.02 to 93.29%. Moreover, structural analogues were investigated and were not indicated to affect the quantification of testosterone. The present method may enable quantification of testosterone in a clinical setting with high precision and accuracy.